2006
DOI: 10.1128/iai.00551-06
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa LecB Is Involved in Pilus Biogenesis and Protease IV Activity but Not in Adhesion to Respiratory Mucins

Abstract: Pseudomonas aeruginosa expresses two lectins which are implicated in adhesion and biofilm formation. In this study, we demonstrate that P. aeruginosa LecB is involved in pilus biogenesis and proteolytic activity. Moreover, neither lectin was involved in adhesion to human tracheobronchial mucin. We infer that some of the ascribed functions are secondary effects on other systems rather than effects of the lectins themselves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 32 publications
1
38
1
Order By: Relevance
“…In addition, it has been demonstrated that LecA induces a permeability defect in the intestinal epithelium, resulting in increased absorption of exotoxin A, an important extracellular virulence factor (19). Additionally, relationships between lectins and other virulence factors have been shown; for example, LecB was shown to be involved in pilus biogenesis and protease IV activity (29).…”
mentioning
confidence: 99%
“…In addition, it has been demonstrated that LecA induces a permeability defect in the intestinal epithelium, resulting in increased absorption of exotoxin A, an important extracellular virulence factor (19). Additionally, relationships between lectins and other virulence factors have been shown; for example, LecB was shown to be involved in pilus biogenesis and protease IV activity (29).…”
mentioning
confidence: 99%
“…Although this surface localization would perfectly explain the influence of LecB on biofilm formation (50), it is in fact not known at present how the protein traverses the cell envelope, since all secretion signals known in P. aeruginosa are missing (30,50). Furthermore, LecB has been shown to influence type IV pilus formation and the extracellular activity of extracellular protease IV, suggesting that this protein may also affect the type II protein secretion of P. (44). Although the role LecB plays in these processes is completely unknown, this context suggests that LecB might exert its influence in the periplasm, which in turn would require a periplasmic localization of the protein itself.…”
Section: Resultsmentioning
confidence: 99%
“…Both lectins were proposed to mediate the adhesion of P. aeruginosa to other bacterial cells of the same or different species (14,62), although this role remains debated (56). LecB was shown to be required for posttranscriptional type IV pilus biogenesis, without impairing transcription of pil genes encoding pilus components (56). LecB was therefore necessary for twitching motility, which occurs on solid surfaces or interfaces by extension and retraction of type IV pili (54).…”
Section: Resultsmentioning
confidence: 99%
“…Since single lecA and lecB mutants of PAO1 showed impaired abilities to form biofilms on abiotic surfaces (14,62), the downregulation of lecA and lecB genes in the algU mutant likely contributes to its biofilm formation defect. Both lectins were proposed to mediate the adhesion of P. aeruginosa to other bacterial cells of the same or different species (14,62), although this role remains debated (56). LecB was shown to be required for posttranscriptional type IV pilus biogenesis, without impairing transcription of pil genes encoding pilus components (56).…”
Section: Resultsmentioning
confidence: 99%